2019
DOI: 10.1097/md.0000000000015903
|View full text |Cite
|
Sign up to set email alerts
|

Variations of plasma D-dimer level at various points of normal pregnancy and its trends in complicated pregnancies

Abstract: D-Dimer (DD) is the smallest fragment of plasmin-mediated cleavage of fibrin. There is a progressive increase in DD concentration with advancing gestation in normal pregnancies, making the upper limit of 0.5 μg/ml used in non-pregnant population an unfavorable marker during pregnancy. Coagulation and fibrinolysis parameters are also markedly disturbed in pregnancies complicated by various pathologies. We designed this retrospective observational cohort study to investigate the trimester specific ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
1
13
0
2
Order By: Relevance
“…However, there have been few studies using a DD + AFP + free β-hCG model to predict HDP in the second trimester. Baboolall et al showed that the AUC of third trimester DD for SPE was 0.828, proving its predictive value for SPE [ 12 ]. The results of our study showed that the AUC values of second trimester DD for GH, PE, and SPE were 0.642, 0.767, and 0.905, respectively, and the AUC values of DD for GH, PE, and SPE were all higher than our previous results for third trimester DD (0.560, 0.614, and 0.640, respectively) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been few studies using a DD + AFP + free β-hCG model to predict HDP in the second trimester. Baboolall et al showed that the AUC of third trimester DD for SPE was 0.828, proving its predictive value for SPE [ 12 ]. The results of our study showed that the AUC values of second trimester DD for GH, PE, and SPE were 0.642, 0.767, and 0.905, respectively, and the AUC values of DD for GH, PE, and SPE were all higher than our previous results for third trimester DD (0.560, 0.614, and 0.640, respectively) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer (DD) is a small protein fragment that is degraded by fibrinolysis. It is the smallest fragment of the fibrin degradation products and increases significantly during pregnancy [ 12 , 13 ]. DD is one of the most valuable indicators for the diagnosis and management of thrombotic states in those with venous thromboembolism, atrial fibrillation, and cancer, as well as those who are pregnant or undergoing surgery.…”
Section: Introductionmentioning
confidence: 99%
“… 24 However, in both complicated and uncomplicated pregnancies, D-dimer levels are known to increase above baseline, although reference ranges are inconsistent. 25 Our study presents novel data on D-dimer trends in SARS-CoV-2–positive symptomatic and asymptomatic women in relation to delivery. CRP has emerged as another independent predictor of adverse outcomes in nonpregnant patients with COVID-19.…”
Section: Commentmentioning
confidence: 96%
“…In the field of pregnancy, the D-dimer concentration has been studied in patients with gestational hypertensive disorders (GHDs). Baboolall et al 22 performed a retrospective observational cohort study of 443 women and concluded that the Ddimer concentration might predict severe preeclampsia (AUC, 0.828). Similarly, Kim et al 23 performed a retrospective cohort study of pregnant women with GHD and noted that patients with severe GHD had significantly higher D-dimer concentrations than those with non-severe GHD.…”
Section: Discussionmentioning
confidence: 99%
“…Baboolall et al. 22 performed a retrospective observational cohort study of 443 women and concluded that the D-dimer concentration might predict severe preeclampsia (AUC, 0.828). Similarly, Kim et al.…”
Section: Discussionmentioning
confidence: 99%